A study of teachers’ pedagogical content knowledge in Kuningan, West Java - Hanggara, Agie; Darsih, Endang (International Journal of Engineering and Technology, 2019)
The problem of this study is the lack of teachers’ pedagogical content knowledge (PCK), in junior high schools in Kuningan, West Java. It’s seen from several facts: first, most of social studies teaching process is conducted separately based on each field without any integration;  second, teachers tend to use monotonous teaching method such as lecturing; third, the lack of ability and skill in using ICT and evaluation system which only focus on students’ cognitive aspect. However, teachers’ pedagogical content knowledge is a vital factor in accomplishing successful teaching and learning outcomes to handle existing educational problems. Therefore, it is crucial to investigate the pedagogical content knowledge of social studies teachers’ in Kuningan. In the present study, 164 social studies teachers from 85 junior high schools in Kuningan were surveyed to find out factors influencing teachers’ pedagogical content knowledge.  The study revealed two important findings: first, teaching experience, training, learning facilities and motivation of teachers have a positive influence on Social Studies teachers’ Pedagogical Content Knowledge (PCK) in Kuningan; second, self efficacy has no influence on Social Studies teachers’ Pedagogical Content Knowledge (PCK) in Kuningan either directly or indirectly.